Two documents of the municipality of Piacenza in the period of the Lombard League (1170-1179) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
Edition of two documents found in a miscellaneous manuscript, deposited at the State Archives of Piacenza.